Opportunities for peak shaving the energy demand of ship-to-shore quay cranes at container terminals - Harry Geerlings; Robert Heij; Ron van Duin (Journal of Shipping and Trade (JST), 2018)
This paper presents the results of both a qualitative and a quantitative study on the possibilities for peak shaving the energy demand of ship-to-shore (STS) cranes at container terminals. The objective is to present an energy consumption model that visualizes the energy demand of STS cranes and to show the possibilities for reducing the peak demand of STS cranes by implementing rules of operation (i.e. changes to the business operational procedures). The results show that the peak demand (and peak-related costs) can be reduced by 50%, with an increase in the handling time of containerships of less than half a minute per hour handling time. This can be achieved by reducing the maximum energy demand of all operating STS cranes or by limiting the maximum number of simultaneously lifting STS cranes. If (one of) these rules of operation is implemented, an intermediate container terminal with six to eight STS cranes can save up to exteuro250,000 per year, which is about 48% of total peak-related energy costs.
Keywords: 650; Peak shaving; Container terminals; Electricity demand; Energy consumption; Ship-to-shore cranes